PENGARUH VARIASI WARNA PLAT KOLEKTOR SURYA TERHADAP KINERJA PEMANAS AIR TENAGA SURYA - SE, Harizalni; Muttaqin, Aris Zainul; Mulyadi, Santoso (ROTOR, 2014)
Solar water heaterÂ  is a deviceÂ  that heats water usingÂ  solar collectors as a heat absorber ofÂ  solarÂ  radiationÂ  that isÂ  transmittedÂ  toÂ  the pipe containing waterÂ  . InÂ  this research, comparative performanceÂ  testing of solar water heating to solar collector plate color variations . Variations of color used is black ( black ) no. ( 39 ) with the brand of quick drying formula zuper spray acrylic spray paint , red ( red signal ) no. ( 23 ) with rj LONDON acrylic paint brand epoxy spray paintÂ  , and blueÂ  ( blueÂ  fluorescentÂ  ) no.Â  ( 1004) with rj LONDON acrylic paint brand spray paint epoxy Data collection was performed byÂ  taking data every 30 minutesÂ  for 3 hours are 9:00 to 12:00 pm at the clock and the test performed 3 times on different days . Data taken from the study include inlet and outlet water temperature collectors , and the temperature of the water in the tank , which is then carried out data processingÂ  to determineÂ  theÂ  flow rateÂ  ,Â  the density of waterÂ  ,Â  the waterÂ  temperature difference in and out collectorÂ  ( ÃTÂ  )Â  ,Â  the performance of solar water heatersÂ  ( qÂ  )Â  , and processingÂ  the data graphically . The results of the study of each color plate solar collector plate showed that the color black has the highest absorption compared with red and blue , because the color black has emissivity close to 1 ( objects that are almost black)Â  is aÂ  transmitter as well as a good heat absorber. Kata kunci: Kolektor, emisivitas, warna plat, air